Antarala of the Sheshashayi Vishnu Temple - Temples of India Project Team (Jio Institute, 2024)
The Sheshashayi Vishnu Temple has an antarala (vestibule) which has empty niches on the lateral sides. The garbhagriha (sanctum sanctorum) has a door with multiple shakhas (vertical bands), but it lacks ornamentation and does not feature a divine figure on the lalatabimba (lintel).